Association of prurigo nodularis and infectious disease hospitalizations: a national cross‐sectional study. (11th July 2021) - Sutaria, N.; Choi, J.; Roh, Y.S.; Alphonse, M. P.; Adawi, W.; Lai, J.; Pollock, J. R.; Fontecilla Biles, N.; Gabriel, S.; Chavda, R.; Kwatra, S. G.
Summary: Background: Prurigo nodularis (PN) is associated with a variety of systemic comorbidities, including infectious diseases such as HIV and viral hepatitis. There are limited data on other infectious disease comorbidities in patients with PN. Aim: To characterize infectious disease hospitalizations among patients with PN and the associated cost burden. Methods: We searched the 2016–2017 National Inpatient Sample, a cross‐sectional sample of 20% of all US hospitalizations, for infectious disease hospitalizations among patients with PN. Associations of PN with infections and related costs were determined using multivariable logistic and linear regression, adjusting for age, race, sex and insurance type. Results: PN was associated with any infection overall (OR = 2.98, 95% CI 2.49–3.56), and with HIV, cutaneous, hepatobiliary, central nervous system, bacterial, viral and fungal/parasitic infections and for sepsis. Patients with PN had a higher mean cost of care (US$11 667 vs. US$8893, P  < 0.001) and length of stay (5.5 vs. 4.2 days, P  < 0.001) for any infection overall and for 7 of 13 other infections. Adjusting for age, race, sex and insurance coverage, PN was associated with higher cost (+30%, 95% CI +17 to +44%) and higher length of stay (+30%, 95% CI +18 to +44%) for any infection overall, and for several specific infections. These associations remained with alternate regression models adjusting for severity of illness. Conclusion: There is a high infectious disease burden among patients with PN, corresponding to higher healthcare utilization and spending. Clinicians must be aware of these associations when treating these patients with immunomodulatory drugs.